2009
DOI: 10.1128/iai.00100-09
|View full text |Cite
|
Sign up to set email alerts
|

The Caspase 1 Inflammasome Is Not Required for Control of Murine Lyme Borreliosis

Abstract: The contribution of the inflammasome to the development of immune responses and disease during infection with the Lyme disease spirochete, Borrelia burgdorferi, is not well defined. Host defense against the spirochete is severely impaired in mice deficient in the adaptor molecule myeloid differentiation antigen 88 (MyD88), which is required not only for Toll-like receptor-mediated responses but also for the production of the proforms of interleukin 1␤ (IL-1␤) and IL-18. These cytokines are released in active f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…While we are unable to formally exclude the possibility of NLRP3 (cryopyrin) or other potential NLRs as potential receptors governing IFN profile induction, the failure of cytosolically administered B. burgdorferi to activate IFN-responsive gene transcription argues against this possibility. In addition, Liu and colleagues recently reported that the inflammasome is not utilized for B. burgdorferi-directed host defense (24). Collectively, our data indicate that B. burgdorferi likely utilizes an (11,14,15,23), induction of IFN-responsive genes by B. burgdorferi-stimulated BMDMs was IRF3 dependent (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…While we are unable to formally exclude the possibility of NLRP3 (cryopyrin) or other potential NLRs as potential receptors governing IFN profile induction, the failure of cytosolically administered B. burgdorferi to activate IFN-responsive gene transcription argues against this possibility. In addition, Liu and colleagues recently reported that the inflammasome is not utilized for B. burgdorferi-directed host defense (24). Collectively, our data indicate that B. burgdorferi likely utilizes an (11,14,15,23), induction of IFN-responsive genes by B. burgdorferi-stimulated BMDMs was IRF3 dependent (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…However, at later time points after Borrelia exposure, caspase-1 might play a different role. Liu et al ., [32] showed that caspase-1 KO mice display higher arthritis scores at day 14 postinfection. On day 45, the arthritis scores in these mice are lower as compared to WT-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…The gram-negative spirochete, Borrelia burgdorferi , a pathogen of chronic Lyme disease-associated arthritis, activates the inflammasome in a manner dependent on ASC and caspase-1, but not NLRP3 (58, 59). In addition, IL-1 is a major pathogenic mediator of Lyme arthritis and is not required for control of Lyme borreliosis in murine models (59, 60). …”
Section: The Pathogenic Roles Of Nlrp3 Inflammasome Activation In Bacmentioning
confidence: 99%